Sistema de Internet das Coisas para Captação de Dados do Microclima Vegetal na Agricultura - Mendes, Davila F.; Carvalho, Claudio Jose R. de; Sousa, Otto Álan P. De; Martins, Marlon Vagner V.; Rocha, Atslands R. da (Proceedings of the Workshop on Computing Applied to the Management of the Environment and Natural Resources (WCAMA); 2023: Proceedings of the 14th Workshop of Applied Computing for the Management of the Environment and Natural Resources, 2023)
The forecast for the planet points to more climate change, increasing the challenge of fighting diseases and pests in agriculture. There is, therefore, a need for greater precision in capturing the climatic elements that directly impact the development of the plant and the intensity of the disease or pest. In this context, we present an Internet of Things (IoT) system for capturing climate data whose differential are sensors placed explicitly in the plant’s microclimate. The microclimate is a relatively small area whose atmospheric conditions differ from the outer zone (e.g., under the canopy of a plant). In this way, studying the dynamics of the climatic elements involved in plant development is possible. One of the applications will be to provide subsidies to predict the disease or pest in the future to carry out preventive management with less use of pesticides.